Impacts of polyethylene microplastics on the performance and mechanism of di-2-ethylhexyl phthalate (DEHP) degradation by two ecotype earthworms - Changhong Yang; Zhen Zhen; Weilong Wu; Guiqiong Yang; Jin Li; Yanqiu Liang; Mengke Song; Dayi Zhang; Zhong Lin; Jing Bai (Ecotoxicology and Environmental Safety)
Di-(2-ethylhexyl) phthalate (DEHP), a ubiquitous agricultural plasticizer, readily leaches into soils. Earthworm-mediated DEHP biodegradation and microplastics (MPs) co-contamination effects on vermicomposting remain uncharacterized. This study evaluated DEHP biodegradation and metabolic pathways in polyethylene microplastic-added soil under earthworm activity. Both epigeic and endogeic ecotypes of earthworms significantly accelerated DEHP degradation. In the treatment without microplastics, the highest degradation efficiency was 72.29 % by endogeic Pheretima guillelmi, while in the treatment with added microplastics, the degradation rate was up to 51.09 %. It was attributing to the increasing soil pH and humus (FA, HA, HM), and the elevated abundance of potential DEHP-degradation microorganisms (Sphingomonas, Lysobacter, and Flavobacterium) and genes (fadA, paaH, and ACAT). Particularly, vermicomposting improved anaerobic benzoyl-CoA degradation pathway, in which Sphingomonas, Lysobacter, and Flavobacterium might carry fadA, paaH, and ACAT genes. Polyethylene-MPs significantly delayed DEHP degradation to 18.48 % in soils without earthworms and 51.09 % in vermicomposting treatments by reducing the abundance of DEHP-degrading microorganisms and genes. Findings revealed polyethylene-MPs effects on earthworm-mediated DEHP degradation and guided agricultural soil management strategies.